Determinants of Food Waste Behavior in Muslim Household Food Consumption in Indonesia - Lubis, Deni; Rodoni, Ahmad; Amalia, Euis (AL-MUZARA'AH, 2024)
Islam forbids wasteful behavior in all activities, yet Indonesia, with the world's largest Muslim population, is the second largest contributor to food loss and waste, with household consumption being the largest contributor. This study examines the factors influencing tabzir (food waste) behavior in Indonesian Muslim households and their relationship with religiosity in reducing tabzir behavior. The method used was a survey of 529 Muslim household respondents, and data analysis was performed using the structural equation modeling–partial least squares (SEM-PLS) approach. The results showed that routine shopping and eating habits had a positive impact on food waste; the worse the shopping behavior and eating habits, the more food wasted. On the other hand, awareness, religiosity, religious norms, and knowledge negatively influence food waste. Thus, the better the level of awareness, knowledge, religiosity, and religious norms, the less food is wasted. While awareness, knowledge, religiosity, and religious norms can help lessen food waste, they are insufficient without regulations on unethical consumption.